Acta Semiotica Estica - Silvi Salupere (Sign Systems Studies, 2022)
Acta Semiotica Estica is an annually published peer-reviewed Estonian-language journal of semiotics based in Tartu, that has been published since 2001. This article gives a brief overview of the history and development of the journal.